Macroeconomic determinants of responsible investments’ performance under different market conditions: Evidence from South Africa - Moodley, Fabian; Lawrence, Babatunde; Kunjal, Damien (Journal of Accounting and Investment, 2024)
Research aims: The study examines the effect of macroeconomic variables on JSE responsible investments returns under changing market conditions.Design/Methodology/Approach: The study implemented a sample period comprising monthly data for the period 2015/11 to 2023/03. The dependent variable of the study comprised of JSE responsible investing indices whereas the independent variables consisted of macroeconomic variables. The study also implemented a two-state Markov regime-switching model to cater to the asymmetrical effect between the dependent and independent variable.Research findings: The JSE responsible investment index returns were found to be significantly positively affected by short-term interest growth rates in a bull regime and significantly negatively in a bear regime. The JSE responsible investment top 30 index returns were significantly negatively affected by the money supply growth rate in a bull regime but not in a bear regime. Moreover, the JSE responsible investment index returns contained alternating efficiencies. Theoretical contribution/Originality: The study is the first to consider the effect of macroeconomic variables on the performance of responsible investments under different market conditions in South Africa. Consequently, the study sheds light on responsible investing in emerging markets where research is limited.Practitioner/Policy implication: Portfolio rebalancing is necessary when equity markets are bullish or bearish. Moreover, policymakers should reconsider market regulations, such that the equity market is adaptive and not efficient. Research limitation/Implication: The study focused on six macroeconomic variables, where this does not affect the robustness of the study. More macroeconomic variables can be used in future research.